OTHR-44. Building narrative competence on the neuro-oncology team: a narrative medicine approach to fostering unity and resilience for work with pediatric brain tumor families. (3rd June 2022) - Riley, Kathy
Abstract: Narrative medicine relies on recognizing, taking in, reflecting on and responding to the stories of suffering in others. Drawing on the practice of the close reading of literature and reflection through writing, healthcare professionals gain fresh insights into their own stories and in turn connect in meaningful ways to stories of illness in their patients (Charon, 2001). The lived experience of pediatric neuro-oncology teams seesaws between hard-fought victories and stories of pain, loss, and even death. For patients who survive, many face life-long challenges that impact long-term quality of life. Learning to be an eyewitness of both beauty and pain in literature and art and writing about that witness helps teams reflect on the stories that shape them and their patients as they process the unthinkable in their work. This type of narrative competence requires what Sayantani DasGuspta refers to as narrative humility (Das Gupta, 2008). Narrative humility recognizes that stories of illness are ambiguous, contain contradictions, and belong wholly to the patient, and encourage providers to explore the role their own narrative brings to the clinician-patient relationship (Das Gupta, 2008). This narrative competence enables team members to find new ways to navigate their practice and foster team unity. Connecting to their own narrative allows them to connect to the narratives of others. They learn to be uncomfortable, to feel pain or joy, and to find power in being physically present with someone who is healed, feels marginalized, or is wounded. By listening closely to the stories of illness and loss in others and reflecting on their own stories through narrative medicine techniques, they learn to engage with the stories that define both their patients and their team dynamics. This theoretical and practical presentation explores the principles of narrative medicine and applies them to the particular experience of neuro-oncology teams.